The voltage-sensing domain of kv7.2 channels as a molecular target for epilepsy-causing mutations and anticonvulsants - Miceli, Francesco; Soldovieri, MariaVirginia; Iannotti, Fabio A.; Barrese, Vincenzo; Ambrosino, Paolo; Martire, Maria; Cilio, Maria R.; Taglialatela, Maurizio (Frontiers in Pharmacology, 2011)
Understanding the molecular mechanisms underlying voltage-dependent gating in voltage-gated ion channels (VGICs) has been a major effort over the last decades. In recent years, changes in the gating process have emerged as common denominators for several genetically-determined channelopathies affecting heart rhythm (arrhythmias), neuronal excitability (epilepsy, pain) or skeletal muscle contraction (periodic paralysis). Moreover, gating changes appear as the main molecular mechanism by which several natural toxins from a variety of species affect ion channel function. In this work, we describe the pathophysiological and pharmacological relevance of the gating process in voltage-gated K+ channels encoded by the Kv7 gene family. After reviewing the current knowledge on the molecular mechanisms and on the structural models of voltage-dependent gating in VGICs, we describe the physiological relevance of these channels, with particular emphasis on those formed by Kv7.2-5 subunits having a well-established role in controlling neuronal excitability in humans. In fact, genetically-determined alterations in Kv7.2 and Kv7.3 genes are responsible for benign familial neonatal convulsions, a rare seizure disorder affecting newborns, and the pharmacological activation of Kv7.2/3 channels can exert antiepileptic activity in humans. Both mutation-triggered channel dysfunction and drug-induced channel activation can occur by impeding or facilitating, respectively, channel sensitivity to membrane voltage and can affect overlapping molecular sites within the voltage-sensing domain of these channels. Thus, understanding the molecular steps involved in voltage-sensing in Kv7 channels will allow to better define the pathogenesis of rare human epilepsy, and to design innovative pharmacological strategies for the treatment of epilepsies and, possibly, other human diseases characterized by neuronal hyperexcitability.